2018
DOI: 10.1016/j.ijrefrig.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical evaluation of different high-temperature heat pump configurations for low-grade waste heat recovery

Abstract: Highlights:  The energy performance and volumetric heating capacity of different vapour compression configurations are compared.  HCFO-1233zd(E), HFO-1336mzz(Z), Butane and n-Pentane are considered as alternative working fluids for HFC-245fa.  The alternatives suggested increase the energy performance in all conditions and configurations.  The proper configuration selection is highly dependent on the temperature lift between the evaporation and condensing temperatures.  n-Pentane achieves the highest COP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…The COP and economic evaluation of HFC‐134a, HFO‐1234yf, HFC‐245fa, HFO‐1336mzz(Z), and HFO‐1234ze(E) at lift temperatures of 30°C and 50°C in high‐temperature heat pump system were investigated by Juhasz; the results indicated that HFO‐1336mzz(Z) has a higher COP and economic justification than that of other working fluids. Mateu‐Royo et al investigated the energy performance and volumetric heating capacity of n ‐pentane, butane, HCFO‐1233zd(E), and HFO‐1336mzz(Z) as low GWP alternative fluids to HFC‐245fa in five high‐temperature heat pump configurations; the results showed that HFO‐1336mzz(Z) achieves medians in these parameters. They also studied the performance of HFO‐1336mzz(Z), HCFO‐1233zd(E), and HCFO‐1224yd(Z) in high‐temperature heat pump system as low GWP alternative fluids to replace HFC‐245fa; the results represented that HFO‐1336mzz(Z) augments the COP about 21% than HFC‐245fa .…”
Section: Introductionmentioning
confidence: 99%
“…The COP and economic evaluation of HFC‐134a, HFO‐1234yf, HFC‐245fa, HFO‐1336mzz(Z), and HFO‐1234ze(E) at lift temperatures of 30°C and 50°C in high‐temperature heat pump system were investigated by Juhasz; the results indicated that HFO‐1336mzz(Z) has a higher COP and economic justification than that of other working fluids. Mateu‐Royo et al investigated the energy performance and volumetric heating capacity of n ‐pentane, butane, HCFO‐1233zd(E), and HFO‐1336mzz(Z) as low GWP alternative fluids to HFC‐245fa in five high‐temperature heat pump configurations; the results showed that HFO‐1336mzz(Z) achieves medians in these parameters. They also studied the performance of HFO‐1336mzz(Z), HCFO‐1233zd(E), and HCFO‐1224yd(Z) in high‐temperature heat pump system as low GWP alternative fluids to replace HFC‐245fa; the results represented that HFO‐1336mzz(Z) augments the COP about 21% than HFC‐245fa .…”
Section: Introductionmentioning
confidence: 99%
“…20. The first observation can be justified attending to that mentioned by Mateu-Royo et al [11], who mentions that the refrigerant with the highest IHX benefit is the one that performs worse in the basic cycle. Then, the similarity between the traditional refrigerant HFC-245fa and the alternative low-GWP refrigerants can be explained attending to the similar thermophysical properties of both fluids, highlighted in Mateu-Royo et al [32].…”
Section: Semi-empirical Low-gwp Refrigerants Assessmentmentioning
confidence: 96%
“…While at lower temperatures, traditional refrigerants such as HFC-134a, HFC-32, and HC-290 can be used in the industry [9], for high-temperature applications other fluids must be considered [10]. Moreover, for higher heat sink temperatures and temperature lifts, the COP can be improved using advanced configurations, different from the basic cycle [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of high temperature HPs, using R717, R365mfc, R1234ze(E), and R1234ze(Z) [12] and R1233zd(E) and 1336mzz(Z) [13], Kondou and Koyama [12] and Mateu-Royo et al [13] evaluated the theoretical performance of different cycle configurations with hydrofluoroolefines in order to demonstrate the potential use of high temperature HPs to recover waste heat and reduce the primary energy consumption.…”
Section: Introductionmentioning
confidence: 99%